First results from the Hertzsprung SONG telescope: asteroseismology of the G5 subgiant star [mu] Herculis - Grundahl, Frank; Karovicova, Iva; Lundkvist, Mia S. (The astrophysical journal, 2017)
We report the first asteroseismic results obtained with the Hertzsprung Stellar Observations Network Group Telescope from an extensive high-precision radial-velocity observing campaign of the subgiant μ Herculis. The data set was collected during 215 nights in 2014 and 2015. We detected a total of 49 oscillation modes with l values from zero to three, including some l = 1 mixed modes. Based on the rotational splitting observed in l = 1 modes, we determine a rotational period of 52 days and a stellar inclination angle of 63°. The parameters obtained through modeling of the observed oscillation frequencies agree very well with independent observations and imply a stellar mass between 1.11 and 1.15 M ⊙ and an age of ##IMG## [http://ej.iop.org/images/0004-637X/836/1/142/apjaa5617ieqn1.gif] $7.8_-0.4^+0.3$ Gyr. Furthermore, the high-quality data allowed us to determine the acoustic depths of the He ii ionization layer and the base of the convection zone.